2020
DOI: 10.3390/cancers12020359
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Germline CYP2W1*6 and CYP2B6*6 Single Nucleotide Polymorphisms on Mitotane Treatment in Adrenocortical Carcinoma: A Multicenter ENSAT Study

Abstract: Mitotane is the only approved drug for advanced adrenocortical carcinoma (ACC) and no biomarkers are available to predict attainment of therapeutic plasma concentrations and clinical response. Aim of the study was to evaluate the suitability of cytochrome P450(CYP)2W1 and CYP2B6 single nucleotide polymorphisms (SNPs) as biomarkers. A multicenter cohort study including 182 ACC patients (F/M = 121/61) treated with mitotane monotherapy after radical resection (group A, n = 103) or in not completely resectable, re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
22
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 30 publications
(24 citation statements)
references
References 39 publications
(100 reference statements)
2
22
0
Order By: Relevance
“…An interesting finding of the present study is that the TTR of plasma mitotane concentrations is able to predict survival, with a higher value associated with longer survival. This was consistent with the previous literature, which established the therapeutic value of mitotane concentrations of 14-20 mg/L [4][5][6][7][8]22]. We adopted the TTR using a concept analogous to warfarin treatment [9] that we Cancers 2020, 12, 740 9 of 13 recently used in a study on adjuvant mitotane treatment [23].…”
Section: Discussionsupporting
confidence: 76%
See 1 more Smart Citation
“…An interesting finding of the present study is that the TTR of plasma mitotane concentrations is able to predict survival, with a higher value associated with longer survival. This was consistent with the previous literature, which established the therapeutic value of mitotane concentrations of 14-20 mg/L [4][5][6][7][8]22]. We adopted the TTR using a concept analogous to warfarin treatment [9] that we Cancers 2020, 12, 740 9 of 13 recently used in a study on adjuvant mitotane treatment [23].…”
Section: Discussionsupporting
confidence: 76%
“…In our study, the overall activity of first-line treatment was limited, with a low number of objective responses (13.7%) and of patients experiencing clinical benefit (23.7%), with no observed difference between patients treated with mitotane + chemotherapy or mitotane monotherapy. We observed that a lower number of patients with advanced ACC benefitted from first-line treatment, either mitotane + chemotherapy or mitotane monotherapy, compared to the FIRM-ACT study and two recent retrospective studies [3,6,22]. However, the present study was not specifically designed to analyze the efficacy of treatment.…”
Section: Discussionmentioning
confidence: 70%
“…This study population of 50 Danish patients has many of the same characteristics as observed in previous studies; a predominantly female cohort with hormone‐producing tumours, mainly secreting cortisol 6,14 . Fifty per cent of patients reached therapeutic levels of mitotane plasma concentration, which is somewhat lower than reported in previous studies 6,10,15,16 . In addition, few or none of the patients in previous studies discontinued mitotane therapy due to side effects 5,6,10,14 as opposed to this study where most patients discontinued treatment mainly due to intolerable side effects.…”
Section: Discussionsupporting
confidence: 54%
“…6,14 Fifty per cent of patients reached therapeutic levels of mitotane plasma concentration, which is somewhat lower than reported in previous studies. 6,10,15,16 In addition, few or none of the patients in previous studies discontinued mitotane therapy due to side effects…”
Section: Discussionmentioning
confidence: 99%
“…Next generation DNA sequencing (NGS) has brought about revolution in genomic research. In the literature, numerous reports can be found proposing comprehensive and novel molecular pathophysiological, diagnostic, therapeutic and prognostic genes associated with ACC [ 4 , 50 , 113 , 141 , 142 , 143 , 144 , 145 , 146 , 147 , 148 , 149 , 150 , 151 , 152 , 153 , 154 , 155 , 156 , 157 , 158 , 159 , 160 ]. Zheng et al have summarized proposed genes as potential drivers involved in sporadic adrenocortical tumorigenesis, including insulin-like growth factor 2, β-catenin (CTNNB1), TP53, ZNRF3 and TERT, as well as novel nominated drivers such as PRKAR1A, RPL22, TERF2, CCNE1 and NF1 [ 161 ].…”
Section: Genetic Analysismentioning
confidence: 99%